Automated DNA Sequencing Requiring No DNA Template Purification. (September 1996) - Chen, Qianfa; Neville, Catherine; MacKenzie, Alex; Korneluk, Robert G.
A critical component in automated fluorescent DNA sequencing is good quality of DNA template. In an effort to reduce the dependence of sequencing success on DNA template quality, the effect of heat-soaked PCR on automated sequencing reactions has been examined. We have found that the heat-soaked PCR protocol considerably improves the overall quality of sequence data and significantly reduces the dependence on the quality of DNA templates. The improvement is corroborated by our ability to obtain over 500 bp of readable sequence per reaction using DNA from E. coli lysates as template obviating DNA purification.